(untitled) (Physical Education, Health and Social Sciences, 2025)
Physical activity plays a vital role in children’s social development, as this study demonstrates by examining its impact on teamwork, communication, and peer relationships. Using a quantitative research design, data was collected from 100 teachers across four schools in Lahore to assess the influence of structured physical activity programs. The findings reveal a significant positive correlation between physical activity and social development, with physical activity accounting for 67.5% of the variance in social skills. This underscores its transformative potential in fostering communication, teamwork, and reducing antisocial behaviors. The study advocates for integrating structured physical activity programs into school curricula to promote holistic development. Future research should employ longitudinal studies to assess sustained impacts and develop diverse, child-centric interventions tailored to various socio-economic contexts.